Analisis Brand Awareness Konsumen Melalui Iklan “Sumba Scarf Signature” Wearing Klamby di Media Sosial - Hannani, Sulis Maulida; Rosmiati, Ana (CITRAWIRA : Journal of Advertising and Visual Communication, 2023)
Abstract :The increase in social media users has made many brands nowadays use it as an advertising medium, especially YouTube and Instagram. Seeing this, the researcher wanted to know the level of brand awareness of ten followers from Klamby's Instagram through the Sumba Scarf Signature ads, which were selected using purposive sampling method. Data collection methods that are applied to this descriptive qualitative research are observation, interviews, and literature study. Then, those data are processed through three stages of Miles and Huberman's interactive analysis. As for analyzing the value and knowing the level of brand awareness, researchers use the theory of David A. Aaker. The results obtained from this study are there is a fairly good response and subject knowledge regarding visual advertisements and the products displayed, and the Klamby brand occupies the position of Brand Recognition in the Brand Awareness pyramidKeywords : Social Media Advertising, Brand Awareness Abstrak :Meningkatnya pengguna media sosial membuat banyak brand kini memanfaatkannya sebagai media periklanan, terutama YouTube dan Instagram. Menilik hal tersebut, peneliti hendak mengetahui bagaimana tingkat brand awareness sepuluh follower Instagram Klamby melalui iklan Sumba Scarf Signature yang diseleksi melalui metode purposive sampling. Metode pengumpulan data yang diterapkan pada penelitian kualitatif deskriptif ini ialah observasi, wawancara, dan studi pustaka. Kemudian, data tersebut diproses melalui tiga tahap analisis interaktif Miles dan Huberman. Adapun untuk menganalisis nilai dan mengetahui tingkat brand awareness, peneliti menggunakan teori David A. Aaker. Hasil yang diperoleh dari penelitian ini ialah adanya tanggapan dan pengetahuan subjek yang cukup baik terhadap visual iklan beserta produk yang ditampilkan, dan brand Klamby menempati posisi Brand Recognition pada piramida Kesadaran Merek.Kata Kunci : Iklan Media Sosial, Kesadaran Merek